Preference of working consumer in Kota Kinabalu on halal products / Dayang Fadzilliah Ramlee and Viola Savia Justine - Ramlee, Dayang Fadzilliah; Justine, Viola Savia (2014)
At the present time, logo and certification of halal are the main issues in Malaysia. This paper focuses on the preference of working consumer in Kota Kinabalu on halal product. The objectives of the research to study the preference on halal products among working consumer in Kota Kinabalu, to evaluate the level of consumers' awareness about the halal products and to measure the association between consumer attitude, awareness, and preference on buying halal product. Cross sectional consumer data were collected in a survey of 147 working respondents in Kota Kinabalu City. Descriptive and inferential analyses were used to analyse the data collected. Thus, there were high preferences on halal products among working consumers in Kota Kinabalu.